Uncovering Coverage: Utilisation of the Universal Health Insurance Scheme, Chhattisgarh by Women in Slums of Raipur - Sulakshana Nandi; Rajib Dasgupta (Indian Journal of Gender Studies, 2016)
This study was conducted in the slums of Raipur, the capital and largest city of Chhattisgarh, with the objective of assessing issues of coverage and utilisation in these areas.
Keywords: Universal health coverage; Gender